2013
DOI: 10.3201/eid1904.121450
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne Encephalitis Virus in Horses, Austria, 2011

Abstract: An unexpectedly high infection rate (26.1%) of tick-borne encephalitis virus (TBEV) was identified in a herd of 257 horses of the same breed distributed among 3 federal states in Austria. Young age (p<0.001) and male sex (p = 0.001) were positively associated with infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 11 publications
4
63
3
Order By: Relevance
“…On the other hand, 77 HI-positive sera must be considered non-specific for USUV, most likely due to the well-known antigenic cross-reactivity of flaviviruses [15,16]. WNV competitive ELISAs may also be used for a combined WNV / USUV / tick-borne encephalitis virus (TBEV) antibody screening, although these assays also show cross-reactions with other flaviviruses and thus the ELISA results must be verified by virus-specific PRNT, too [17]. Although WNV had never been observed in Switzerland and it emerged in Austria not before 2008 [18,19], i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, 77 HI-positive sera must be considered non-specific for USUV, most likely due to the well-known antigenic cross-reactivity of flaviviruses [15,16]. WNV competitive ELISAs may also be used for a combined WNV / USUV / tick-borne encephalitis virus (TBEV) antibody screening, although these assays also show cross-reactions with other flaviviruses and thus the ELISA results must be verified by virus-specific PRNT, too [17]. Although WNV had never been observed in Switzerland and it emerged in Austria not before 2008 [18,19], i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The PRNT-90 against WNV was carried out as described above for USUV, but with WNV strain Eg101 [17]. …”
Section: Methodsmentioning
confidence: 99%
“…Due to the known cross reactivity between WNV and other flaviviruses, selected ELISA-positive samples (n = 48) were re-tested by WNV lineage 2-specific PRNT-90 as previously described [14,15].…”
Section: Methodsologymentioning
confidence: 99%
“…According to the National Center for Zoonotic Diseases (NCZD), five of the most prevalent zoonotic diseases in Mongolia include tickborne rickettsiosis, anthrax, rabies, tick-borne encephalitis, and brucellosis. Worldwide, horses have been found to be carriers for all five of these diseases (Rushton et al 2013, Turner et al 1999, Merini et al 2010, Moraes Filho et al 2009, Santos et al 2016, Tahamtan et al 2010) and have been found specifically to carry rabies, anthrax, and brucellosis in Mongolia (Odontsetseg et al 2009, Zolzaya et al 2014, Odontsetseg et al 2007. A similar study rating the risks of zoonotic disease in Mongolia to humans and livestock found brucellosis, rabies, and anthrax to be three of the top four most important diseases, with the fourth being echinococcosis (McFadden et al 2016).…”
Section: Introductionmentioning
confidence: 99%